PENGARUH LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI PUSKESMAS LAU KABUPATEN MAROS - Eka Suci Maharani Rivai; Agung Widhi Kurniawan; Zainal Ruma (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the effect of the work environment on the work discipline of employees at the Lau Public Health Center, Maros Regency. The independent variable in this study is the work environment, while the dependent variable is work discipline. The population in this study were all employees of the Lau Public Health Center, Maros Regency as many as 57 employees with a sampling technique with saturated sampling technique. Data collection was done by using a questionnaire. The data analysis technique used is simple linear regression analysis using SPSS 22.00 for windows. Based on the results of the study obtained a simple regression equation Y = 8.475 + 0.785X. The results of the t-test hypothesis obtained that the t-count value of the work environment variable is greater than the t-table value with a significance level of 0.000 <0.05, which means that the work environment has a positive and significant effect on work discipline. The result of the coefficient of determination test (R2) is 0.563, which means that the ability of the work environment variable in explaining work discipline to Lau Health Center employees is 56.3% while the rest is explained by other variables that were not examined in this study.